JARINGAN VOIP (VOICE INTERNET PROTOCOL) MENGGUNAKAN METODE CME (CALL MANAGER EXPRESS) PADA ROUTER - Aziz Setyawan (Paradigma, 2012)
Selection methods in addition to functioning as an infrastructure is also seen process information from other advantages. Methods of infrastructure development is the construction of a computer network that can accommodate and satisfy all kinds of information delivery and also can save on the cost or expenses of a business. CME (Call Manager Express) router with VoIP method can provide some similar features of the system Private Brand Exchange (PBX) plus the number ofdata and routing capabilities.Keywords: Networking, VoIP (Voice Over Internet Protocol), CME (Call Management Express).